An application of soft set theory in decision making problem by parameterization reduction - Maharana, Manamohan; Mohanty, Debudutta (Soft computing (Berlin, Germany), 2021)
In this paper, we concentrate the application of parametric reduction of soft set in decision making problem. The main purpose of the paper is to select the key parameters for selection or purchase of objects. Using key parameters person or selection committee will select the optimal choice object. We put forward an algorithm in decision making problem and provide some examples. We focus on parameter reduction of soft set and how it helpful in effective and efficient decision making of the people in a short time.